2016
DOI: 10.21829/myb.1999.521345
|View full text |Cite
|
Sign up to set email alerts
|

Variación en el patrón de crecimiento en altura de cuatro especies de Pinus en edades tempranas

Abstract: Con el propósito de determinar la variación inter e intraespecífica en la tasa de crecimiento en altura y el número de ciclos, se evaluó una plantación experimental de 18 meses de edad, establecida en Patoltecoya, Puebla, durante un periodo de 12 meses. La plantación incluye un total de 30 procedencias de 4 especies de Pinus (10 de P. greggii Engelm., 11 de P. patula Schl. et Cham., 4 de P. tecunumanii (Schw.) Eguiluz et Perry y 5 de P. maximinoi H. E. Moore), en un diseño experimental de parcelas divididas en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…In this study, P. patula populations originating, in general, at mid-low and mid altitudes had a higher growth potential, which seems to be characteristic of this species (SALAZAR-GARCÍA, 1999). However, the population from the extreme lowest altitude (2400 m) had poorer growth performance than other populations from similar altitudes.…”
Section: Discussionmentioning
confidence: 46%
“…In this study, P. patula populations originating, in general, at mid-low and mid altitudes had a higher growth potential, which seems to be characteristic of this species (SALAZAR-GARCÍA, 1999). However, the population from the extreme lowest altitude (2400 m) had poorer growth performance than other populations from similar altitudes.…”
Section: Discussionmentioning
confidence: 46%
“…Height growth was related to the altitude, rainfall and dry season of the seed origin [41], and the greatest growth would occur in populations originating from 1255 m a.s.l., with populations from either lower or higher altitudes having a lower growth [42]. Pinus patula provenances from lower altitudes showed higher growth and a larger number of shoots cycles than provenances from higher altitudes [43,44]. However, in a greenhouse-provenance trial, seedlings showed slightly higher growth potential in provenances from mid-altitude (2700 m a.s.l.)…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that P. patula provenances from lower altitudes have a higher growth [43]. In our study, there is a correlation among seed origin rainfall and the mean value of the first factor (r = 0.65), related to stem mass fraction, and SLA and the plasticity in the second factor (r = 0.63), related to root and stem dry biomass, indicating that even at local scales there is an adaptive pattern to climate of the integrated phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In plantations, P. greggii shows it is well adapted to several ecological conditions, particularly in semiarid conditions (López and Muñoz 1991) and degraded soils (López-Peralta and Sánchez-Cabrera 1996). In favorable conditions, its height and radius show high growth rates (Salazar et al 1999). Plantations of P. greggii have also been established in other countries such as Argentina, Venezuela, South Africa, and Zimbabwe (Dvorak and Donahue 1992).…”
Section: Introductionmentioning
confidence: 99%